1991
DOI: 10.1093/nar/19.15.4121
|View full text |Cite
|
Sign up to set email alerts
|

Rapid DNA sequencing by horizontal ultrathin gel electrophoresis

Abstract: A horizontal polyacrylamide gel electrophoresis apparatus has been developed that decreases the time required to separate the DNA fragments produced in enzymatic sequencing reactions. The configuration of this apparatus and the use of circulating coolant directly under the glass plates result in heat exchange that is approximately nine times more efficient than passive thermal transfer methods commonly used. Bubble-free gels as thin as 25 microns can be routinely cast on this device. The application to these u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(29 citation statements)
references
References 5 publications
(1 reference statement)
0
29
0
Order By: Relevance
“…Closing (8)(9)(10) and reusable capillary gels (11,12) reduce the sequencing electrophoresis time to <1 hr and the detection limit to a few thousand fluorescent molecules per band (10-20 mol), the modular primers can be expected to decrease the time per walking cycle to 1 or 2 hr from the time of several days it now takes.…”
Section: Discussionmentioning
confidence: 99%
“…Closing (8)(9)(10) and reusable capillary gels (11,12) reduce the sequencing electrophoresis time to <1 hr and the detection limit to a few thousand fluorescent molecules per band (10-20 mol), the modular primers can be expected to decrease the time per walking cycle to 1 or 2 hr from the time of several days it now takes.…”
Section: Discussionmentioning
confidence: 99%
“…This concern arose because MicroCel gels are relatively thin (50 mm), are cast by a rapid photopolymerization process, and are cast between ÂȘunpassivatedÂș (uncoated) glass plates which could contribute strong interfacial effects. While an earlier study of comparably thin slab gels revealed no electrophoretic anomalies [76], we decided to carefully re-examine the issue with MicroCel gels. In a later publication, we will present a detailed study of the factors which limit the electrophoretic resolution on MicroCel gels.…”
Section: Limits Imposed By the Physics Of Electrophoresis On Microcelmentioning
confidence: 99%
“…Chen and co-workers [8] reported the use of 0.1±1 mM To-Pro-3 complexing agent in capillary gel electrophoresis-mediated DNA fragment separation using a 640 nm solid-state red diode laser. Combination of the benefits of slab and capillary gel electrophoresis resulted in high-performance ultrathin gel electrophoresis, a novel and highly efficient multilane separation platform which was first introduced for DNA sequencing [9,10] and later for DNA fragment analysis [11]. This technique also enables separation enhancement and labeling of the migrating dsDNA molecules by noncovalent complexation with intercalator dyes, such as ethidium bromide, SYBR Green, Cascade Blue and To-Pro-3.…”
Section: Introductionmentioning
confidence: 99%